The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1016/s0014-5793(02)02521-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ten exon deleted ERβ mRNAs in human ovary, breast, uterus and bone tissues: alternate splicing pattern of estrogen receptor β mRNA is distinct from that of estrogen receptor α

Abstract: Four different human tissues and breast cancer cell lines were screened to identify exon deletion variant transcripts of estrogen receptor L L (ERL L) by reverse transcription-polymerase chain reaction using the 'splice targeted primer approach' that amplifies each category of exon deleted variants as a separate gene population. A total of 10 different variant mRNAs that have deletions in various combination of exons were identified by sequence analysis. They were exon 2v v; exons 2 and 5^6v v; exon 3v v; exon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
5

Year Published

2004
2004
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 40 publications
1
64
0
5
Order By: Relevance
“…31,32 Interestingly, in breast, 25 ovary 25-28 and endometrium, 29 malignancy is associated with loss of ERb expression while in adenocarcinoma of the esophagus 30 increased expression is seen. One study has shown decreased ERb expression in colonic adenocarcinoma 31 while another study 32 suggests that, as [33][34][35] as well as evidence that the interaction of ERa and ERb levels may play a role in carcinogenesis. 28 The demonstration of ERb in vascular neoplasms suggests a role for estrogen antagonists in the therapy of the most aggressive vascular tumors: angiosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Interestingly, in breast, 25 ovary 25-28 and endometrium, 29 malignancy is associated with loss of ERb expression while in adenocarcinoma of the esophagus 30 increased expression is seen. One study has shown decreased ERb expression in colonic adenocarcinoma 31 while another study 32 suggests that, as [33][34][35] as well as evidence that the interaction of ERa and ERb levels may play a role in carcinogenesis. 28 The demonstration of ERb in vascular neoplasms suggests a role for estrogen antagonists in the therapy of the most aggressive vascular tumors: angiosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…all of the cell lines were found to express a 52-54 kda protein (the reported size for Erβ1). certain cell lines also expressed a smaller molecular weight band that may be an Erβ spliced variant (46,(57)(58)(59).…”
Section: Er Mrna Expression Using Rt-pcrmentioning
confidence: 99%
“…MCF-7 cells have an epithelial morphology, are adherent, and form a monolayer in culture. These cells express both estrogen receptor (ER)α and ERβ (Brooks et al, 1973, Enmark et al, 1997, Fuqua et al, 1999, Leygue et al, 1999, Fasco et al, 2000, Poola et al, 2000, Yoshida et al, 2000, Lespagnard et al, 2001, Poola et al, 2002 and (WT) PTEN (Li et al, 1998, Lu et al, 1999, Weng et al, 1999, Clark et al, 2002. MCF-7 cells were obtained from the American Type Culture Collection (ATCC) (Manassas, VA).…”
Section: Cell Culturementioning
confidence: 99%